Dynamic foot plantar measurement platform using optical sensors - Nampeng, Jindapa; Visitsattapongse, S.; Pintavirooj, C. (My University, 2017)
Foot plantar pressure is the interface pressures between the foot surface and the supporting surface during daily activities. Pressure information provides valuable insight in gait and posture research for diagnosis diseases, footwear design, sport performance, injury prevention and other applications. In this paper, a dynamic foot plantar pressure measurement platform is proposed suitable for measuring dynamic plantar pressure in real-time with high accuracy and reliability. A Platform has made from steel structure covering with 15 mm acrylic plate with LED strip on the top and surrounding by 3 mm black acrylic to block undesirable light. The optical sensors, the infrared cameras, have connected on Raspberry Pi to process and record plantar pressure frame in avi file using OpenCV library.
Keywords: Foot plantar pressure; Image Processing; Optical sensors